2002
DOI: 10.1185/030079902125000840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food on Early Drug Exposure from Extended-Release Stimulants: Results from the Concerta®, Adderall XR™ Food Evaluation (CAFÉ) Study

Abstract: Stimulant therapy is the mainstay of treatment for children, adolescents and adults with attention-deficit/hyperactivity disorder (ADHD). Once-daily, extended-release oral formulations offer long acting control of symptoms by modifying drug delivery and absorption. In particular, consistency in early drug exposure is important for symptom control during school or work hours. Because these once-daily formulations are usually taken in the morning, the timing of the doses with breakfast is important. This study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Metadate 1 capsules contains 30% IR beads and 70% DR beads, and when administered once daily produces a methylphenidate plasma concentration profile similar to that of IR methylphenidate taken twice daily. The bioavailability of methylphenidate was not shown to be altered when the capsules were administered by sprinkling their contents onto a small amount of applesauce [17]. Concerta 1 tablets are coated with IR methylphenidate and contains an osmotic pumop (OROS) that gradually releases the drug over a 10 h period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metadate 1 capsules contains 30% IR beads and 70% DR beads, and when administered once daily produces a methylphenidate plasma concentration profile similar to that of IR methylphenidate taken twice daily. The bioavailability of methylphenidate was not shown to be altered when the capsules were administered by sprinkling their contents onto a small amount of applesauce [17]. Concerta 1 tablets are coated with IR methylphenidate and contains an osmotic pumop (OROS) that gradually releases the drug over a 10 h period.…”
Section: Discussionmentioning
confidence: 99%
“…Enrollment of children into clinical studies that require the use of invasive procedures is always a major concern. In this study, a relatively large number of blood samples (17) were required to be taken from each subject over three 24 h periods post administration, and therefore adults were chosen as the subjects of the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, drug exposure for methylphenidate from the Concerta ® formulation was not affected by food. The authors concluded less variability in drug exposure in patients taking Concerta ® compared to Adderall XR ® particularly if meal intake varied (10). Although these results were challenged because the study compared partial area AUCs as opposed to traditional BE criteria, it illustrates how food effect data can also be used to promote market advantage between drugs in a therapeutic class (11).…”
Section: Introductionmentioning
confidence: 97%
“…Significant variations in the plasma levels of d-amphetamines were reported when one compared their administration with and without food intake (Adderall XR) 26,27 . It has been demonstrated in vitro that the solubility of LDX is not affected by pH within a physiologically relevant range (pH = 1-8), and is slightly reduced when the pH is substantially increased (pH = 8-13) 20 .…”
Section: Pharmacokineticsmentioning
confidence: 99%